PROBLEMS OF LEGAL REGULATION OF DEFINITION OF THE NOTIONS "CORPORATE RELATIONS” AND "CORPORATE RIGHTS” - Kurinskyi, Oleksandr Heorhiiovych (ВЕРХОВЕНСТВО ПРАВА, 2017)
The article is dedicated to analysis of provisions of Ukrainian laws containing definitions of such notions as “corporate relations” and “corporate rights”, as well as provisions of the laws, where such notions are used. The article pinpoints defects and inconsistencies in legal regulation of the above issues and proposes ways and approaches to improvement of the provisions of the law.